Decreased NK cell immunity in kidney transplant recipients late post-transplant and increased NK-cell immunity in patients with recurrent miscarriage - Zhu, Li; Aly, Mostafa Gaafa; Morath, Christian; Kuon, Ruben-Jeremias; Opelz, Gerhard; Daniel, Volker (PLOS ONE, 2017)
Background There is evidence that NK-cell reactivity might affect graft outcome in transplant recipients and pregnancy in women. Method NK-cell subsets were determined in whole blood using eight-colour-fluorescence flow cytometry in patients before and after renal transplantation, patients with recurrent miscarriage (RM) and healthy controls (HC). Results Patients late post-transplant (late-Tx) with functioning renal transplants showed abnormally low CD56dimCD16+ NK-cells containing both perforin and granzyme (vs HC p = 0.021) whereas RM patients exhibited abnormally high numbers of these cells (vs HC p = 0.043). CD56dimCD16+perforin+granzyme+ NK-cell counts were strikingly different between the two patient groups (p<0.001). In addition, recipients late-Tx showed abnormally low CD8+ NK-cells (vs HC p<0.001) in contrast to RM patients who showed an abnormal increase (vs HC p = 0.008). CD8+ NK-cell counts were strongly different between the two patient groups (p<0.001). Higher perforin+granzyme+CD56dimCD16+ and CD8+ NK-cells were associated with impaired graft function (p = 0.044, p = 0.032). After in-vitro stimulation, CD56dimCD16+ and CD56brightCD16dim/- NK-cells showed strong upregulation of CD107a and IFNy, whereas the content of perforin decreased dramatically as a consequence of perforin release. Recipients late post-Tx showed less in-vitro perforin release (= less cytotoxicity) than HC (p = 0.037) and lower perforin release was associated with good graft function (r = 0.738, p = 0.037). Notably, we observed strong in-vitro perforin release in 2 of 6 investigated RM patients. When circulating IL10+CD56bright NK-cells were analyzed, female recipients late post-Tx (n = 9) showed significantly higher relative and absolute cell numbers than RM patients (p = 0.002 and p = 0.018, respectively); and high relative and absolute IL10+CD56bright NK-cell numbers in transplant recipients were associated with low serum creatinine (p = 0.004 and p = 0.012) and high glomerular filtration rate (p = 0.011 and p = 0.002, respectively). Female recipients late post-Tx exhibited similar absolute but higher relative numbers of IL10+IFNy- NK-cells than RM patients (p>0.05 and p = 0.016, respectively). Conclusion NK-cells with lower cytotoxicity and immunoregulatory function might contribute to good long-term graft outcome, whereas circulating NK-cells with normal or even increased cytotoxicity and less immunoregulatory capacity are observed in patients with RM.
Gesehen am 04.04.2018